2015
DOI: 10.1016/j.triboint.2015.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nanosilica additive particles on both friction and wear performance of mild steel/CuSn/SnBi multimaterial system

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. This paper presents an experimental study of the tribological behaviour of a multimaterial system using conventional powder metallurgy process with SiO 2 nanoparticles. Four configurations were studied with and without SiO 2 . The tribological properties of the sintered materials were analysed by wear experiments at lubricated conditions on a ball disc wear tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…where x ii Qε and y jj Qε respectively represent the X and Y coordinates of the point Q ε in {W}, and Z coordinate of Q ε corresponds to the matrix element Z(ii Q ε ,jj Q ε ); t ξ * and θ i * respectively represent the corresponding cutting time (s) and axial positional angle (degree) with respect to p*; as shown in Figure 8, ∆t and ∆θ are the cutting time increment (s) and the axial positional angle increment (degree) of Q ε with respect to the calculating vertex p*; and ∆x and ∆y are the coordinate increments (mm) in the X and Y directions, respectively, which can be directly calculated. Equation (15) can be converted to…”
Section: Simulation Methods For Ball-end Trochoidal Milling Micro Surface Topographymentioning
confidence: 99%
See 1 more Smart Citation
“…where x ii Qε and y jj Qε respectively represent the X and Y coordinates of the point Q ε in {W}, and Z coordinate of Q ε corresponds to the matrix element Z(ii Q ε ,jj Q ε ); t ξ * and θ i * respectively represent the corresponding cutting time (s) and axial positional angle (degree) with respect to p*; as shown in Figure 8, ∆t and ∆θ are the cutting time increment (s) and the axial positional angle increment (degree) of Q ε with respect to the calculating vertex p*; and ∆x and ∆y are the coordinate increments (mm) in the X and Y directions, respectively, which can be directly calculated. Equation (15) can be converted to…”
Section: Simulation Methods For Ball-end Trochoidal Milling Micro Surface Topographymentioning
confidence: 99%
“…An important aspect of surface quality, micro surface topography refers to the irregular micro geometry such as surface roughness, waviness, shape error, and texture [12], which not only affects surfaces' wear, lubrication state, friction coefficient, etc., but also other properties of the parts' contact state [13][14][15]. Trochoidal milling has complex trajectories and consequently forms micro surfaces via complicated mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the requirements of surface hardness and wear resistance are becoming higher. [1][2][3][4][5] Chemically bonded phosphate ceramic coatings (CBPCs), as a kind of inorganic coating with great potential, has attracted great attention. [6][7][8][9] Recently, many studies have reported carbon nanotubes (CNTs) can act as a good nanofiller to enhance the wear and corrosion resistance property of the coating due to their unique features such as excellent mechanical, thermal and electrical properties.…”
mentioning
confidence: 99%